Effect of Seed Priming on Seedling Vigour and Yield of Tomato and Chilli - Maiti, Ratikanta; Rajkumar, Dasari; Jagan, Mangalarapu; Pramanik, K.; Vidyasagar, P. (International Journal of Bio-resource and Stress Management, 2023)
Seed priming increases seedling vigour of several vegetable crops. Tomato (Lycopersicon esculentunm L.) and chilli (Capsicum annuum L.) were tested for seed priming at seedling stage (4 tomato and 3 chilli varieties) under lab and vegetative and reproductive sate at field conditions (2 tomato and 2 chilli varieties). The priming techniques improved seedling vigour, growth and yield of tomato and chilli although varieties showed variation in response to different treatments. Especially halopriming increased speed of emergence, seedling vigour index, root length and shoot length over hydropriming in tomato and chilli. At field level halo priming showed better performance than control and hydropriming. Halo priming caused early flowering in tomato (8149, 8152) and chilli (9357). Increased plant height is also noticed in halopriming with respect to tomato and chilli (8149, 8152, 9357 and 9366). Mostly importantly halopriming increased total yield 20 plants-1 in tomato and chilli. This is the first observation in the aspect of increased yield under field condition with respect to seed priming in vegetable crops.